The Effect of Leaflet Media to Students Knowledge about Scabies in the Yanbu’ul Qur’an 1 Pati Boarding School - Purnamasari, Rina; Retmono, Retno Indrastiti; Nazah, Eilsha Kholidatun (Nusantara Science and Technology Proceedings, 2024)
The background to this research is, scabies is a skin disorder that causes discomfort due to lesions that are very itchy so sufferers often scratch and cause infection. In terms of age, scabies tends to occur more frequently in children and adolescents. Islamic boarding schools are one of the environments with a high incidence and prevalence of scabies in Indonesia. Therefore, efforts to increase students’ knowledge about scabies can be done through educational activities. The aim of this research is to determine the effect of leaflet media on students’ knowledge about scabies at the Yanbu’ul Qur’an 1 Pati Islamic Boarding School. The research was conducted in June 2023-March 2024, the type of quantitative research was analytical with a One Group Pretest-Posttest design. The research respondents were class VII students at the Yanbu’ul Qur’an 1 Pati Islamic Boarding School for the 2023 academic year. Taken through Simple Random Sampling with the inclusion of 88 respondents. The results of this research show that 73 respondents’ posttest scores increased compared to the pretest after education. Therefore it can be concluded that, there is an influence of leaflet media on the knowledge Students about scabies in Boarding school Yanbu'ul Qur'an 1 Pati.